2009
DOI: 10.1186/1471-2164-10-348
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic-based identification of maternal proteins in mature mouse oocytes

Abstract: BackgroundThe mature mouse oocyte contains the full complement of maternal proteins required for fertilization, reprogramming, zygotic gene activation (ZGA), and the early stages of embryogenesis. However, due to limitations of traditional proteomics strategies, only a few abundantly expressed proteins have yet been identified. Our laboratory applied a more effective strategy: one-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis (1D SDS-PAGE) and reverse-phase liquid chromatography tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 60 publications
4
80
2
1
Order By: Relevance
“…Previous MS studies on mice analysed the proteome of mature oocytes , Zhang et al 2009) and processes of oocyte maturation (Vitale et al 2007, Cao et al 2012, Monti et al, 2013 in young donors, but not oocyte quality and composition during maternal ageing. As MS is not inherently quantitative, Wang et al (2010) relied on the simultaneous comparison of signal intensities between replica samples from young donors, in a so-called label-free approach that requires high numbers of oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous MS studies on mice analysed the proteome of mature oocytes , Zhang et al 2009) and processes of oocyte maturation (Vitale et al 2007, Cao et al 2012, Monti et al, 2013 in young donors, but not oocyte quality and composition during maternal ageing. As MS is not inherently quantitative, Wang et al (2010) relied on the simultaneous comparison of signal intensities between replica samples from young donors, in a so-called label-free approach that requires high numbers of oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, several approaches analyzing the protein composition of oocytes have been conducted to obtain the proteome signatures of Xenopus, bovine, pig, and mouse oocytes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Calvert et al (15) identified eight highly abundant heat shock proteins and related chaperones in the mature mouse egg by two-dimensional difference gel electrophoresis (DIGE).…”
mentioning
confidence: 99%
“…The number of mammalian genes that have been classified as maternal effect thus far is significantly less than the number of proteins one would expect to be necessary for pre-EGA embryonic development (Yurttas et al, 2010;Zhang et al, 2009). There are potentially many reasons for this, but I will consider five.…”
Section: Maternal Effect Genesmentioning
confidence: 99%